Prevalence of internet addiction among medical and non-medical students of International Islamic University Malaysia (IIUM), Kuantan - Azmi, Fatin Nadrah; Jasmani, Norshahida; Mohd Salim, Fatin Salina; Abdul Hadi, Azwanis; Azmi, Nurul Husna; Abd. Aziz, Karimah Hanim (IIUM Press, 2023)
Internet addiction has become a serious problem with the increasing internet use, especially among college students and adolescents. Most of the available literature on internet addiction among college students was mainly related to medical students and showed a disturbing prevalence, however, this is not widely studied among non-medical students. This study describes the prevalence and factors associated with internet addiction among medical and non-medical students at International Islamic University Malaysia (IIUM), Kuantan. A total of 107 medical and 104 non-medical students of IIUM Kuantan participated in this crosssectional study conducted from July 15, 2019, to August 25, 2019, using random sampling. The Internet Addiction Test (IAT) was distributed through social media platform. Descriptive statistics were used to describe the prevalence and socio-demographic characteristics of the respondents, while binary logistic regression was used to identify respondents’ factors associated with internet addiction. The results showed that 67.3% of medical students and 65.4% of non-medical students were moderately addicted to the Internet. The significant predictors of internet addiction in medical students are age (OR 0.235 95% CI 0.068-0.812) and duration of internet use of 4-6 hours (OR 0.235 95% CI 0.068-0.812). Among non-medical students, the significant predictors were social networking (OR 0.137 95% CI 0.003-0.636), Internet TV (OR 3.574 95% CI 1.057-12.08), and time spent on the Internet from 4-6 hours (OR 0.247 95% CI 0.06-0.91). The prevalence of internet addiction among medical and non-medical students at IIUM Kuantan is of concern. Early identification based on these findings for each medical and non-medical faculty can be tailored to ensure successful intervention.